2020
DOI: 10.7554/elife.64739
|View full text |Cite
|
Sign up to set email alerts
|

Shedding light on those who provide support

Abstract: An eLife survey explores the experiences of those in the research community who support colleagues struggling with their mental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…This highlights the need to provide assistance and training for those providing the support. [5] If an individual's mental health is not a priority, they may ultimately end up leaving their institution, resulting in a loss of diversity and talent. This is supported by a recent Nature survey of postdoctoral researchers, where 51 % had considered leaving science due to anxiety, depression, or similar issues related to their work.…”
Section: Why Mental Health Mattersmentioning
confidence: 99%
“…This highlights the need to provide assistance and training for those providing the support. [5] If an individual's mental health is not a priority, they may ultimately end up leaving their institution, resulting in a loss of diversity and talent. This is supported by a recent Nature survey of postdoctoral researchers, where 51 % had considered leaving science due to anxiety, depression, or similar issues related to their work.…”
Section: Why Mental Health Mattersmentioning
confidence: 99%
“…For instance, institutions and funding agencies that do not encourage the traditional gender roles allowing both men and women to take family leave, see better work-life balance, and reduced work-life conflict [63,64]. If the culture in your research lab constrains your ability to manage your work-life balance in a way you find satisfactory, shifting departmental and institutional attitudes and policies can put pressure on PIs to build a more supportive work culture via steps outlined elsewhere [11,12,[31][32][33]. Although organizational culture cannot be changed overnight, changes in policy can go a long way in creating a culture that aids work-life balance in the academic workplace [62][63][64].…”
Section: Rule 10: Open a Dialogue About The Importance Of Work-life Balance And Advocate For Systemic Changementioning
confidence: 99%
“…Departments and institutes need to contribute to improving research practices for academics at all levels on the career ladder [29,30]. PIs and mentors can promote healthier environments in their laboratories by respecting boundaries and providing individuals with greater autonomy over their own working schedule [11,12,[31][32][33]. However, institutions do not typically prioritize work-life balance, leading to the loss of valuable talent in the research pipeline.…”
mentioning
confidence: 99%
“…Solutions may lie in providing more training for supervisors and trainees, raising awareness across all research-related entities-from institutions to funding agencies-and in defining new processes to rate and measure scholastic performance. As one 2019 study has put it: "Ensuring that all supportersnot just group leadersreceive help, training and recognition may be key to fostering healthy, positive relationships between those who provide and receive support" (Loissel, 2020). In fact, training research scientists to become better mentors has been shown to improve the quality of undergraduate research experience and enhance the quality of undergraduate research (Pfund et al, 2006), which reinforces the need to infuse the scientific system with this kind of practice.…”
Section: Closing Remarks and Outlookmentioning
confidence: 99%